2011
DOI: 10.1182/blood-2011-04-348839
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 enables cross-presentation by multiple dendritic cell subsets through a type I IFN-dependent pathway

Abstract: Conjugation of TLR agonists to protein or peptide antigens has been demonstrated in many studies to be an effective vaccine formula in inducing cellular immunity. However, the molecular and cellular mediators involved in TLR-induced immune responses have not been carefully examined. In this study, we identify Type I IFN and IL-12 as critical mediators of crosspriming induced by a TLR7 agonistantigen conjugate. We demonstrate that TLR7-driven cross-priming requires both Type I IFN and IL-12. Signaling through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 50 publications
(65 reference statements)
4
94
0
Order By: Relevance
“…For cross-priming CD8 + T cell responses, attention has been focused on introducing Ags to CD8a + DCs, or equivalent cells in humans, through targeting cell surface receptors, such as CD205 (54)(55)(56)(57). Other investigators are conjugating Ags directly to TLR ligands that target these same cells (58)(59)(60). However, we showed that through exposure to different stimuli, including from NKT cells, different DC subsets can become involved.…”
Section: Cd8amentioning
confidence: 88%
“…For cross-priming CD8 + T cell responses, attention has been focused on introducing Ags to CD8a + DCs, or equivalent cells in humans, through targeting cell surface receptors, such as CD205 (54)(55)(56)(57). Other investigators are conjugating Ags directly to TLR ligands that target these same cells (58)(59)(60). However, we showed that through exposure to different stimuli, including from NKT cells, different DC subsets can become involved.…”
Section: Cd8amentioning
confidence: 88%
“…Conversely, several studies suggest that multiple DC subsets are required to induce optimal T-cell immunity. 73,74 These and other studies also describe a dependency on type I IFN in raising efficient immune responses, which can be produced by various cell types such as pDCs, myeloid DCs, monocytes, or stromal cells. [75][76][77][78] Together with the controversy over which DC subset may or may not present the best target, this argues against targeting vaccines to single APC subsets and justifies the question: "Targeting DCs-why bother?…”
Section: Codelivery Of Antigens and Adjuvants By Suitable Vaccine Carmentioning
confidence: 94%
“…Type I IFNs are induced primarily during viral infections and have been shown to promote NK cell, Th1 cell, and, in particular, CTL responses through stimulation of Ag cross-priming (71) and DC maturation (72)(73)(74)(75). It has been reported that type I IFNs are crucial factors regulating the accumulation of DCs in lymph nodes and their maturation into activated APCs during a TLR7-driven response (76). They are also required for intratumoral accumulation of the CD8a + cDC subset (48) and for their ability to develop antitumoral immunity (75) + T cell responses to cell-associated Ags.…”
Section: Discussionmentioning
confidence: 99%